IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM KEGIATAN PEMBELAJARAN IPA DI KELAS IV SDN 2 KABILA KABUPATEN BONE BOLANGO - Bima Sanjaya Putra Langkau; Meylan Saleh; Gamar Abdullah; Kudus; Isnanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Differentiated instruction is an instructional approach designed to accommodate differences in students’ readiness levels, interests, and learning profiles, and is particularly relevant to elementary science education characterized by diverse learner backgrounds. This study aimed to describe the implementation of differentiated instruction in fourth-grade science classes at SDN 2 Kabila, Bone Bolango Regency, to identify the challenges faced by teachers, and to examine the implementation of assessment practices within differentiated learning. This research employed a qualitative descriptive design. The participants consisted of a fourth-grade teacher and fourth-grade students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that differentiated instruction was implemented through differentiation of content, process, product, and learning environment, and contributed to increased student engagement and motivation in science learning. However, several challenges were identified, including limited instructional time, a relatively large class size, and the complexity of comprehensive assessment. Assessment practices included diagnostic, formative, and summative approaches, although further optimization is required. In conclusion, differentiated instruction plays a significant role in fostering inclusive and meaningful science learning at the elementary school level.